2019
DOI: 10.2147/opth.s209942
|View full text |Cite
|
Sign up to set email alerts
|

<p>Efficacy and safety of tafluprost 0.0015% – retrospective analysis of real-world data from the Philippines</p>

Abstract: PurposeTo investigate the IOP lowering effect and safety of tafluprost 0.0015% in a routine clinical setting in the Philippines.Patients and methodsA retrospective review of glaucoma patients receiving tafluprost 0.0015% (BAK 0.001% preserved) with a minimum follow-up of 3 months was conducted. Main outcome measure was the mean IOP change at month 3. Secondary outcome measures included longitudinal IOP assessments and occurrence of any adverse events.ResultsThree-hundred twenty-nine eyes of 177 patients with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
0
10
1
Order By: Relevance
“…A recent retrospective study has reported that tafluprost was safe and showed the effective IOP lowering, which was sustained up to 12 months post-treatment. 41 The previous studies also showed that preserved PF-tafluprost significantly decreased the symptoms and signs of OSD when compared to latanoprost. 11,22 The result of this current study was similar to these previous studies reported.…”
Section: Discussionmentioning
confidence: 89%
“…A recent retrospective study has reported that tafluprost was safe and showed the effective IOP lowering, which was sustained up to 12 months post-treatment. 41 The previous studies also showed that preserved PF-tafluprost significantly decreased the symptoms and signs of OSD when compared to latanoprost. 11,22 The result of this current study was similar to these previous studies reported.…”
Section: Discussionmentioning
confidence: 89%
“…A retrospective study of patients treated with tafluprost 0.0015% in a routine clinical setting in the Philippines, which included 329 eyes in 177 patients, found that the majority of patients (≥85%) reported no adverse effects over a mean follow-up period of 8.8 months. The rates of eye redness and conjunctival hyperemia were 10% and 15%, respectively [ 21 ]. No patients discontinued treatment due to adverse symptoms or signs during the study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous switch studies conducted on Asian eyes have been retrospective studies looking at varying glaucoma diagnoses, or prospective studies involving patients switched from different classes of medications or from a specific eyedrop only. 20,21 This study has the advantage of being a prospective study specifically evaluating POAG and OH patients switching from preserved PGA class to PF tafluprost in a multiethnic Asian population. Even though most glaucoma patients can tolerate preserved PGAs, a large number of patients do suffer from OSD caused by preservatives, specifically BAK.…”
Section: Discussionmentioning
confidence: 99%